POROZUMIENIA ZAKŁADOWE (BETRIEBSVEREINBARUNGEN) W PRAWIE NIEMIECKIM - Gładoch, Monika (Zeszyty Prawnicze, 2017)
Works Agreements in the German Law Summary The article discusses specific agreements in the German collective labor law. They are concluded between a staff committee and an employer. In the German law the priority is given to the collective agreements. Works agreements play a major role in the German enterprises, not only because of they legal identity but also as a regulatory means. They play the most important role in the German concept of codetermination. Works agreements are made for all employees of a given institution.